ESTETIKA TARI PERSEMBAHAN DI BUMI LANCANG KUNING - Nabila, Nabila Muna Mufidah (Indonesian Journal of Islamic Studies (IJIS), 2025)
This article discusses the offering dance at Bumi LancangKuning. The purpose of this article is to discuss the aesthetic values ​​that exist in the performance dance itself. The method used in this article uses a descriptive qualitative method. In accordance with what has been researched by researchers, the aesthetic value of this performance dance is the movements, costumes, music and also the atmosphere created during the performance. There are many meanings implied in this, such as a form of respect for the guests, then the music that accompanies it also makes the atmosphere more solemn and peaceful when looking at it. And the dancers wear sacrificial dance attire which adds aesthetic value to it, not only that, their graceful movements also add to the aesthetic values ​​of the sacrificial dance.